MAPPING SUBSURFACE FORMATIONS ON THE EASTERN RED SEA COAST IN JORDAN USING GEOELECTRICAL TECHNIQUES: GEOLOGICAL AND HYDROGEOLOGICAL IMPLICATIONS - Batayneh Awni T. (Earth Sciences Research Journal)
During 2006, geoelectrical measurements using the vertical electrical sounding (VES) method were conducted on the eastern Red Sea coast in Jordan, using the SYSCAL-R2 resistivity instrument. The objectives of the study were (i) to evaluate the possibility of mapping of Quaternary sediments medium in areas where little is known about the subsurface geology and to infer shallow geological structure from the electrical interpretation, and (ii) to identify formations that may present fresh aquifer waters, and subsequently to estimate the relationship between groundwater resources and geological structures. Data collected at 47 locations were interpreted first with curve matching techniques, using theoretically calculated master curves, in conjunction with the auxiliary curves. The initial earth models were second checked and reinterpreted using a 1-D inversion program (i.e., RESIX-IP) in order to obtain final earth models. The final layer parameters (thicknesses and resistivities) were then pieced together along survey lines to make electrical cross sections. Resistivity measurements show a dominant trend of decreasing resistivity (thus increasing salinity) with depth and westward toward the Red Sea. Accordingly, three zones with different resistivity values were detected, corresponding to three different bearing formations: (i) a water-bearing formation in the west containing Red Sea saltwater; (ii) a transition zone of clay and clayey sand thick formation; (iii) stratas saturated with fresh groundwater in the east disturbed by the presence of clay and clayey sand horizons. Deep borehole (131 m) drilled in the northwestern part of the study area for groundwater investigation, has confirmed the findings of the resistivity survey.